THE RIGHT TO PRIVACY IN EMPLOYMENT AND ITS PROTECTION UNDER THE EUROPEAN CONVENTION ON HUMAN RIGHTS - Kalamatiev Todor; Ristovski Aleksandar (Faculty of Law Iustinianus Primus in Skopje, 2020)
The right to privacy in employment and the protection of the privacy of workers in general, is gaining increasing importance in the information and knowledge-based society. Tectonic changes in the world of work involving new technologies and forms of communication are also shaping the methods of supervision and control performed by employers in the working process. The new methods of surveillance and control through which employers exercise their managerial prerogatives include various forms of electronic surveillance over the use of computers (e.g. Internet access, e-mail), telephones and mobile phones, video surveillance, GPS location and the like. Privacy in the field of employment relations can be problematized in other ways and through the application of other methods too (processing personal data of employees, body checks, medical screening, psychological and polygraph testing, etc.). Hence, modern legal systems face increasing challenges in establishing the appropriate level of balance between protecting workers’ fundamental right to privacy on the one hand, and employers' property rights and managerial prerogatives on the other. In this regard, major concerns are raised about the admissibility and limits of the intrusion of employers into the private life of workers. In this paper, the right to privacy in employment will be analyzed through the prism of Council of Europe regulations (primarily Article 8 of the European Convention on Human Rights) and the jurisprudence of the European Court of Human Rights. The authors will address two important issues: the scope of the right to privacy in the context of employment (ie in which situations, employees have the right to protection of their privacy) and the scope of protection against intrusion into the right to privacy of workers (ie in which situations, employers have the right to justified interference). In addition, other relevant regulations of the Council of Europe and the European Union relating to the protection of the right to privacy, and above all those relating to the protection of personal data, will be taken into account. Despite the negligible legal framework that regulates the right to privacy in the context of employment in North Macedonia and the modest case law in this area, the authors of this paper give a critical review of existing regulations and offer de lege ferenda solutions for better and more efficient regulation on this relatively new but extremely important domain of the employment relationships.